An attempt at standardization of nursing care in case of lower legs venous ulcerations - Trzaszczka, Magdalena; Gorzkowicz, Bożena (Nursing Problems / Problemy Pielęgniarstwa, 2007)
In Poland, similarly to Western European countries, new institutions and health centers come into being formed by groups of specialists. In this centers leg lower ulcerations are treated complexity, which is supported by deep theoretical knowledge and practical experience of all therapeutic team members. The special role is attributed to nurses specializing in surgical, family and preventive medicine. They possess appropriate skills and qualifications in the field of venous ulcerations treatment. One of the most important factors influencing poor development of this kind of specialist proceedings is lack of guidelines to this type of treatment. Venous ulcerations are a big social problem especially in a group of old and lonely people. Disease contributes to decreasing sick person’s quality of life by function disorders. It results in increasing psychological, social, occupational and cultural problems, too. Distribution and importance of this problem give reasons for working out a standard of care for patients suffering from leg ulcer.